Examen especial al programa 35 obras públicas del Gobierno Autónomo Descentralizado del Cantón Pallatanga, periodo 2021. - Granizo Olmedo, Yadira Genevive (2024)
ABSTRACT: The present research work had as objectives to apply the phases of the special examination to the program 35 Public Works of the GAD of the Canton Pallatanga, period 2021 and establish the degree of compliance with the laws, regulations and other current regulations to the execution of public works, through the application of the inductive, deductive and analytical method, with a type of documentary and field research, In turn, a non-experimental design and a qualitative approach are contemplated, the population consisted of 5 officials of the Department of Public Works and documentary population, preliminary visit interviews were applied to the highest authority of the entity and the OOPP area, with this general information was obtained, also 5 internal control questionnaires were used to evaluate the level of risk, confidence that presents the GAD of Pallatanga. The main results show that the municipality only executed 72.52% of the budget allocated for 2021, which corresponds to USD 3,000,506.81, therefore, there is a deviation of 27.48% equivalent to USD 1,136,809.19 affecting the fulfillment of the work called “Implementation of the storm sewerage system and treatment plant of the urban head of the Canton Pallatanga”. It is worth mentioning that for the 2021 period, 11 public works were planned, of which 10 were carried out, leaving the aforementioned project unfinished.